Research on the Ore-controlling Factors and Ore-prospecting Indicators of Gaoaobei Tungsten Mines in Rucheng County of Hunan Province. (June 2020) - Tian, Junwei; Tian, Xufeng; Yan, Fugui; Liu, Yangsheng; Xiao, Lin; Li, Wenchao; Cao, Zhijun
Abstract: By means of comprehensive analysis, the Gaoaobei tungsten mines in Rucheng County was studied and the results showed that: 1) the ores occurred in veins. The major ore minerals were black-tungsten ores, followed by molybdenite, cassiterite, chalcopyrite, stannite, native bismuth, etc. 2)Distribution of the ore bodies were mainly affected by the formation, the structure and magmatism; 3) There were quite a lot of obvious direct ore-prospecting indicators in the region, mainly including abandoned mining workings, quartz vein, alteration, structural feature.